2021
DOI: 10.3389/fonc.2021.575425
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Chromatin Accessibility Analysis Based on Different Immunological Subtypes of Clear Cell Renal Cell Carcinoma

Abstract: BackgroundRecent research of clear cell renal cell carcinoma (ccRCC) is focused on the tumor immune microenvironment (TIME). Chromatin accessibility is critical for regulation of gene expression. However, its role in different immunological subtypes of ccRCC based on immune cell infiltration has not been systematically studied.MethodsFive hundred thirty patient data from The Cancer Genome Atlas Kidney Renal Clear Cell Carcinoma (TCGA-KIRC) were adopted to estimate immune cell infiltration. Twenty-four types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Overall, ccRCC is characterized by increased inflammation and angiogenesis, which further promote tumor metastasis and recurrence. Shiqiang et al 62 analyzed 530 tumor samples and found that the existence of Tregs, activated DCs (aDCs), CD58 + NK cells, and Th2 cells was related to the poor prognosis of patients with ccRCC ( P < .05). Th17 cells, neutrophils, mast cells, NK cells, γδ T cells, and central memory T cells were associated with good prognosis in ccRCC ( P < .05).…”
Section: Targeting the Immune System And Immune Metabolismmentioning
confidence: 99%
“…Overall, ccRCC is characterized by increased inflammation and angiogenesis, which further promote tumor metastasis and recurrence. Shiqiang et al 62 analyzed 530 tumor samples and found that the existence of Tregs, activated DCs (aDCs), CD58 + NK cells, and Th2 cells was related to the poor prognosis of patients with ccRCC ( P < .05). Th17 cells, neutrophils, mast cells, NK cells, γδ T cells, and central memory T cells were associated with good prognosis in ccRCC ( P < .05).…”
Section: Targeting the Immune System And Immune Metabolismmentioning
confidence: 99%
“…Epigenomic aberrations in RCC have attracted increased attention recently 12 14 . In particular, chr.3p, whose loss is a typical genomic aberration in ccRCC, contains several chromatin modifiers, such as PBRM1, SETD2, and BAP1, and these genetic mutations are also frequently observed in the contralateral allele 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, bioinformatics algorithms are developed for an immune infiltration estimation of a series of cancer tissues based on their transcriptional data ( Hänzelmann et al, 2013 ; Yoshihara et al, 2013 ; Newman et al, 2015 ). These methods have significantly promoted our understanding of the TME and have been applied to hepatocellular carcinoma ( Liu S. et al, 2021 ), clear cell renal cell carcinoma ( Zhang et al, 2021 ), pancreatic adenocarcinoma ( Liu et al, 2020 ), and so on. However, the application of retinoblastoma has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%